The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pin.12761
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, controversies and the future of prostate cancer grading

Abstract: Histological grading of prostate cancer is one of the most important tissue‐based parameters for prediction of outcome and treatment response. Gleason grading remains the foundation of prostate cancer grading, but has undergone a series of changes in the past 30 years, often initiated by consensus conference decisions. This review summarizes the most important modifications that were introduced by the 2005 and 2014 International Society of Urological Pathology (ISUP) revisions of Gleason grading and discusses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(118 reference statements)
1
4
0
Order By: Relevance
“…This parameter is highly correlated with the aggressiveness of the malignancy, and highly aggressive tumors progress more rapidly and are usually associated with LN metastasis. In our study, the XGB model showed that the weight value of GS was the highest, showing the importance of this parameter and indicated that it contributed most to the results obtained ( 40 , 41 ). As our results demonstrated, the XGB model assigned weighted values to all variables and arranged them by order of importance, thus allowing for more variables to be involved in the analysis and helping physicians to better understand the risk factors.…”
Section: Discussionsupporting
confidence: 56%
“…This parameter is highly correlated with the aggressiveness of the malignancy, and highly aggressive tumors progress more rapidly and are usually associated with LN metastasis. In our study, the XGB model showed that the weight value of GS was the highest, showing the importance of this parameter and indicated that it contributed most to the results obtained ( 40 , 41 ). As our results demonstrated, the XGB model assigned weighted values to all variables and arranged them by order of importance, thus allowing for more variables to be involved in the analysis and helping physicians to better understand the risk factors.…”
Section: Discussionsupporting
confidence: 56%
“…Histological grading of prostate cancer is an important parameter for predicting the treatment and prognosis response. To date, Gleason grading forms the basis of prostate cancer grading (Egevad et al, 2019). The Gleason grade is assigned based on the architecture and arrangement of the malignant cells within the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Gleason score takes into account the two most common cell subtypes rather than the worst pattern, which can lead to underestimation of the aggressiveness of the tumour. Additionally, different rules exist for reporting Gleason scores in biopsy specimens, which can lead to undergrading the tumour compared with radical prostatectomy biopsy [152][153][154] . Gleason score is further categorized into one of five prognostic ISUP groups, ranging from 1 (low risk) to 5 (high risk) 56 , with group 1, 2, 3, 4 and 5 tumours corresponding to Gleason scores ≤3+3, 3+4, 4+3, 4+4, and ≥4+5, respectively 56 .…”
Section: [H2] Pathologymentioning
confidence: 99%